Pemanfaatan Media Wordwall Sebagai Kecerdasan Buatan Dalam Menumbuhkan Perilaku Responsif Siswa Kelas VIII Pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 2 Jetis Ponorogo - Indah Puspita, Silvia Putri; Agnibaya, Rangga (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to describe the application of wordwall media in grade VIII, wordwall media can foster responsive student behavior, and forms of responsive behavior that grow through wordwalls. The method used is qualitative with a case study research type. To collect data, the researchers conducted interviews, observations, and documentation. The data was analyzed using the Miles Huberman and Saldana model through condensation by selecting and simplifying the data that had been collected, so that the data collected was stronger, then the data was presented to understand the overall situation, which then the researcher could plan the next steps. Furthermore, the expected conclusions can be drawn with this to find new findings. To find out whether the data obtained can be trusted and relied on, the researcher carried out source triangulation by checking data from various data sources such as the principal, curriculum vice principal, subject teachers and grade VIII students. The results show that Wordwall is applied in three stages: pre-implementation, implementation, and evaluation. The interactive quiz challenges stimulate student participation and foster cognitive (responding to peers' answers), affective (enthusiasm in answering), and social (refuting incorrect answers) responsiveness. In conclusion, Wordwall effectively enhances student engagement and responsiveness and serves as a relevant digital tool in improving the quality of classroom learning